ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN DALAM PENENTUAN NISBAH BAGI HASIL SIMPANAN DEPOSITO MUDHARABAH DAN PERLAKUAN AKUNTANSINYA PADA BPR SYARIAH ASRI MADANI NUSANTARA - Hisamuddin, Nur; A, Andi (BISNIS, 2015)
This title of this research, namely analysis that Infuenced considered in the determination of the odds for the results of Deposit Mudharabah deposits and His Accounting Treatment on Bpr Syariah Asri Civil Society of the Archipelago. The purpose of this research is as follows: to know the factors that are considered in the determination of the odds for the results of deposit mudharabah on BPR Syariah Asri Civil Society Nusantara, to know the recognition and measurement, presentation and disclosure of deposit mudharabah on BPR Syariah Asri Civil Society archipelago have been in accordance with the PSAK 105. Qualitative research method descriptive analysis. Research Results concluded that the factors that are considered in the determination of the odds for the results of deposit mudharabah on BPR Syariah Asri Civil Society of the archipelago is the rate that applies in other sharia banks and conventional banks based on financial performance; good relationship between bank with a partner or client; the work plan of the annual budget and the placement of the funds between Bank (inter-city in the whole of Indonesia); macro economic.